Measuring spatio-temporal disparity of location-based accessibility to emergency medical services - Xiong, Qiangqiang; Liu, Yaolin; Xing, Lijun; Wang, Liye; Ding, Yimei; Liu, Yanfang (Health & place, 2022)
The importance and sensitivity of the time dimension in the emergency medical service (EMS) field have been widely recognized in recent years. However, the EMS spatio-temporal disparity remains partially uncovered in traditional accessibility measurements due to EMS's context-sensitive characteristics and demand specificity. In this study, we obtained dynamic traffic conditions and realistic EMS demand from online map services and historical emergency calls-out data, and then developed three location-based spatio-temporal EMS accessibility measurements. The empirical results demonstrate that the three different spatio-temporal EMS accessibility have a complex relationship, and are beneficial for measuring the EMS spatio-temporal disparity in different scenarios with distinct competitive effects. Ultimately, we emphasized four original EMS accessibility patterns, which helped us uncover significantly well-served or underserved areas. This study contributes to optimize the layout of EMS resources by understanding the regularity of EMS spatio-temporal disparity. •Dynamic traffic conditions and realistic EMS demand.•Three location-based spatio-temporal accessibility measurements have been developed.•EMS spatio-temporal disparity in different scenarios with distinct competitive effects.•Uncover significantly well-served or underserved areas of EMS.